Optimation of Combination of N-Hexane Solution and Ethyle Acetate on Secondary Metabolite Compounds Profile of Streptomyces hygroscopicus - Dio Giovanni Ariel; Sri Winarsih; Fitria Febriliani Putri; Nabila Erina Erwan; Ajeng Maharani Putri; Alfian Wika Cahyono; Kana Mardhiyyah; Loeki Enggar Fitri; Rivo Yudhinata Brian Nugraha (Fakultas Kedokteran Universitas Brawijaya, 2021)
Streptomyces hygroscopicus (S.hygroscopicus) is a Gram-positive soil bacterium that can produce secondary metabolites from fermentation that have a therapeutic effect. The fermented S. hygrocospicus metabolites that are still in the form of crude extracts are difficult to develop as drug preparations because the active compounds are not yet known, so it will be challenging to determine the dosage of drugs that have a therapeutic effect. Therefore, it is necessary to carry out exploratory research to narrow down the secondary metabolite profile from the fermentation of S. hygroscopicus, using extraction and fractionation methods, which are then identified by Thin-Layer Chromatography (TLC) using a combination of solvents. This study used the extraction method with a separating funnel. The fractionation was carried out using the BUCHI (SepacoreÂ®) Flash Chromatography and RevelerisÂ® PREP Purification System column chromatography gradually using ethyl acetate and n-hexana.Â 47 and 60 of the fractionation results were taken as samples, that further were profiled using TLC and given the appearance of 10% KOH stains and p-Anisaldehyde - sulfuric acid, so that various classes of compounds with different Rf values were obtained, namely Monoterpenes, Triterpenes, Steroids, Saponins, Coumarin, Scopoletin, and Alkaloids.